Using camera trapping data to calculate diversity, activity pattern and relative abundance of terrestrial mammals at Lambir Hills National Park - Phyllis, Lahang (Universiti Malaysia Sarawak (UNIMAS), 2005)
A study on terrestrial mammals was conducted using camera traps between February 2004 till September 2004 in Lambir Hills National Park, Miri, Sarawak to calculate diversity, activity pattern and relative abundance. Six. CamTrakker and one unit DeerCam was used with total effort of 1127 trap-night. A total of 269 wildlife photos record was obtained. A total of209 terrestrial mammals were recorded comprising five orders, 10 families and 17 species. M. nemestrina recorded the highest frequency of photos in this area with 59 exposures and the highest RAJ of 0.282. Six. species were recorded with single exposure; A. binturong, E. gymnwus, P. linsang, R. macro tis, S. barbatus, and M. fascicularis and has the lowest RAJ of 0.005. M. nemestrina and Muntiacus sp were active in diurnal while Tragulus sp, V. tangalunga and T. crassispinis were active in nocturnal.